SYNTHESIS AND ANALGETIC ACTIVITY EVALUATION OF 4-[N-(4-HYDROXYPHENYL)CARBOXYMIDOYL]-2-METHOXYPHENOL - Pudjono, Pudjono; Anindita, Jessica; Hakim, Arief Rahman; Purnomo, Hari (INDONESIAN JOURNAL OF PHARMACY, 2016)
Paracetamol is an analgesic-antipyretic compound derived from p-aminophenol. Though paracetamol has good efficacy and safety on consumption, parasetamol has hepatotoxic effect as its     adverse drug reaction. 4-[N-(4-hydroxyphenyl)carboxymidoyl]-2-methoxyphenol is one of p-aminophenol derivative that was already been determined in silico using molecular docking PLANTS method, and it was known that 4-[N-(4-hydroxyphenyl) carboxymidoyl]-2-methoxyphenol has analgesic effects more potent and has hepatotoxic adverse effect lower than paracetamol. 4-[N-(4-hydroxyphenyl)carboxymidoyl]-2-methoxy-phenol can be synthesized through reaction of p-aminophenol with vanillin under acid condition. The synthesized products were recrytalized, dried, and the purity was determined with melting point determination and Thin Layer Chromatography. The structure of pure crystals were elucidated using IR, 1H-NMR, C-NMR, and Mass Spectroscopy. The analgesic evaluation was carried in vivo using writhing test method. The synthesized compound were divided into three dosage variations, 0,5; 1; and 2 mol equivalent to 100 mg/kgBB of paracetamol (reference drug). 4-[N-(4-hydroxyphenyl)carboxymidoyl]-2-methoxyphenol with 1 mol dosage has analgesic activity better than paracetamol but the difference was not significant.Keywords: 4-[N-(4-hydroxyphenyl)carboxymidoyl]-2-methoxyphenol, p-aminophenol, analgesic, writhing test